Robots in the classroom: Differences in students' perceptions of credibility and learning between "teacher as robot" and "robot as teacher". (December 2016) - Edwards, Autumn; Edwards, Chad; Spence, Patric R.; Harris, Christina; Gambino, Andrew
Abstract: Advancements in technology are bringing robotics into interpersonal communication contexts, including the college classroom. This study was one of the first to examine college students' communication-related perceptions of robots being used in an instructional capacity. Student participants rated both a human instructor using a telepresence robot and an autonomous social robot delivering the same lesson as credible. However, students gave higher credibility ratings to the teacher as robot, which led to differences between the two instructional agents in their learning outcomes. Students reported more affective learning from the teacher as robot than the robot as teacher, despite controlled instructional performances. Instructional agent type had both direct and indirect effects on behavioral learning. The direct effect suggests a potential machine heuristic in which students are more likely to follow behavioral suggestions offered by an autonomous social robot. The findings generally support the MAIN model and the Computers are Social Actors paradigm, but suggest that future work needs to be done in this area. Highlights: Both "teacher as robot" and "robot as teacher" were rated as credible instructors. The teacher as robot (telepresence teacher) was rated as most credible. The robot as teacher (autonomous social robot) produced more behavioral learning. Robotic "displacing technologies" may create positive learning attitudes. Robotic "replacing technologies" may be more effective for influencing behavior.